Stent Applications for Palliative Treatment in Advanced Stage Esophageal Cancers - Mustafa Şentürk; Murat Çakır; Mehmet Aykut Yıldırım; Ömer Kişi (Gastroenterology Research and Practice)
Background and Aim. Endoscopic stenting is a generally safe and effective palliative treatment for esophageal malignancies. In this study, we aimed to present endoscopic stent applications, adverse events, and relative advantages of covered versus uncovered stents in our center. Methods. We examined cases of endoscopic stenting for palliative treatment of advanced stage esophageal cancers between January 2014 and July 2019. Age, gender, location of mass, adverse events, survival time, and stent type were evaluated. Outcomes of fully covered and uncovered self-expanding stents were compared with regard to adverse events, including stent migration and occlusion. Results. The mean age of the patients was 66.4±1, 52 were male, and 8 were female. Patients were followed up for a mean of 133 days. The most common complication due to stenting was migration. 13 patients developed adverse events. Migration was the most common adverse event, occurring in 8 (13%) patients. Although the migration rate of fully covered stents was higher than uncovered stents, there was no statistically significant difference (p=0.47). Stent occlusion was observed in 4 patients. In three cases, it was due to the tumor; an uncovered stent was placed again in these cases. Food-related occlusion developed in one patient. There was no statistical difference in terms of overall adverse event rate when comparing fully covered stents to uncovered stents (p=0.68). Conclusion. Endoscopic stenting is a viable palliative method with low morbidity and mortality in experienced centers. Though there are relative advantages with covered versus uncovered stents in individual cases, the overall adverse event rate is low and relatively similar.